Synthesis of Novel Magnetic Water-Soluble Chitosan as Potential Magnetic Resonance Imaging Contrast Agents - Zhang, Xiaoyan; Zhao, Yingying; Han, Tongwei; Zhang, Qi (Asian Journal of Chemistry, 2013)
A magnetic water-soluble chitosan as potential contrast agents for MRI was synthesized by a simple new route. The morphology and structure of the magnetic water-soluble chitosan were characterized by FTIR, FESEM and XRD. The magnetic properties were characterized by in vitro and T2-weighted FLASH image experiments. In vitro magnetic resonance imaging demonstrates that the magnetic water-soluble chitosan could greatly enhance the contrast for image under magnetic field and the contrast was enhanced with the concentration. The results of T2-relaxivities indicates that the magnetic water-soluble chitosan provided high relaxivity. The paper presents a new, simple and economic route to preparing magnetic water-soluble chitosan using for potential magnetic resonance imaging contrast agents.